Improving the Climate Hazards Group Infrared Precipitation (CHIRP) using WHU-SGCC method over the Jinsha River Basin from 1990 to 2014 - Shen, Gaoyun; Chen, Nengcheng; Wang, Wei; Chen, Zeqiang (Supplement to: Shen, G et al. (2019): WHU-SGCC: a novel approach for blending daily satellite (CHIRP) and precipitation observations over the Jinsha River basin. Earth System Science Data, 11(4), 1711-1744, https://doi.org/10.5194/essd-11-1711-2019, 2019)
A daily precipitation estimation derived from WHU-SGCC method (Wuhan University Satellite and Gauge precipitation Collaborated Correction), blending daily precipitation gauge data and the Climate Hazards Group Infrared Precipitation (CHIRP, daily, 0.05°) satellite-derived precipitation estimates over the Jinsha River Basin during the different seasons from 1990 to 2014.
Keywords: Bias correction; CHIRP; WHU-SGCC